2019
DOI: 10.3390/en12183509
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Analysis of Malaysian Macroalgae Biomass as Potential Feedstock for Bio-Oil Production

Abstract: The potential of Caulerpa lentillifera, Gracilaria coronopifolia and Chaetomorpha linum, as biomass feedstock was investigated in this study. It was concluded that seaweed is more suitable for bio-based products synthesis, i.e., bioplastic and bio-lubricants, instead of biofuels due to its relatively low calorific value (~12 MJ/kg). Since seaweed has high moisture content (~80%), hydrothermal liquefaction is recommended, and its efficiency can be further enhanced through microwave technology. Besides, it is fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…At the higher heating rate, the reaction time became shorter and, hence, a higher temperature was required for the evolution of volatiles from the biomass samples, whereas at a low heating rate, a longer residence time and greater instantaneous energy were available for the volatiles evolved from the biomass (Waheed et al, 2015). In line with our findings, Ong et al (2019) reported a low calorific value for algae and excellent mechanical and thermal properties and suggested their use for the production of biopolymers. The authors also performed TGA of the algal biomass in this study, where three species of seaweed used as a feedstock were exposed to different heating rates of 10°C, 20°C, and 30°C/min.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…At the higher heating rate, the reaction time became shorter and, hence, a higher temperature was required for the evolution of volatiles from the biomass samples, whereas at a low heating rate, a longer residence time and greater instantaneous energy were available for the volatiles evolved from the biomass (Waheed et al, 2015). In line with our findings, Ong et al (2019) reported a low calorific value for algae and excellent mechanical and thermal properties and suggested their use for the production of biopolymers. The authors also performed TGA of the algal biomass in this study, where three species of seaweed used as a feedstock were exposed to different heating rates of 10°C, 20°C, and 30°C/min.…”
Section: Discussionsupporting
confidence: 87%
“…Marine algae are currently being exploited in different industries (El Semary, 2020;El Semary, 2021), the most recent application of which is bioplastic production (Abdul Khalil et al, 2017;El Semary, 2021). (Gai et al, 2013;Ling et al, 2016;Bin Yusoff, 2017;Youning et al, 2018;Abdo and Ali, 2019;Amin et al, 2019;Ong et al, 2019;Filiciotto andRothenberg, 2021 andNikiema andAsiedu, 2022) Algae and plants usually contain starch and cellulose as the starting materials for bioplastic formation, which are completely biodegradable (Abdul Khalil et al, 2017;Devadas et al, 2021;Zanchetta et al, 2021). Macroalgae can be used in the formation of bioplastics mostly through using their derivatives (Devadas et al, 2021;Zanchetta et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The peak around 1429 cm −1 could be attributed to the aromatic structure’s C–C stretching vibration. The peak at 1083 cm −1 is typical of aliphatic amines’ C–N and C–O–C stretching vibrations, indicating the presence of proteins and polysaccharides [ 46 , 47 ]. The FTIR spectra show that raw seaweed displayed high stretching vibration peaks corresponding to the O–H and N–H groups (3454 cm −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Brown seaweed are considered versatile and can be sustainably used as a potential source for various applications worldwide including biomass feedstock, conversion into green biofuels, aqua and animal feed, active ingredients in the pharmaceutical and nutraceutical products along with integration in the human food chain (Chia et al ., 2018; Ong et al ., 2019; Biris‐Dorhoi et al ., 2020). Brown seaweed has been used as a dietary and functional food for centuries, especially in Asian countries where consumption can reach 1 kg of dry weight per person annually (Tamama, 2021).…”
Section: Introductionmentioning
confidence: 99%